Silesian Debate: The Upper Silesian Tragedy of 1945: Victims and Perpetrators (Zaranie Śląskie, 2025)
On 6 March 2025, a debate entitled The Upper Silesian Tragedy of 1945: Victims and Perpetrators was held at the Silesian Library, organised by the Institute of Regional Studies of the Silesian Library. The discussion focused on attempts to define who the victims and perpetrators were, as well as on responsibility for the crimes and repressions carried out in 1945. The debate addressed, among other issues, the actionsof the Red Army after its entry into Upper Silesia, the operation of labour and internment camps, including those in Świętochłowice-Zgoda and Łambinowice, as well as the deportations of the civilian population to the Soviet Union. Participants emphasised the multidimensional nature of the violence, resulting both from the systemic mechanisms of Soviet authority and the communist security apparatus, and from local social conditions and national tensions.
Keywords: Upper Silesian Tragedy; 1945; Upper Silesia; labour camps; deportations to the USSR